2019
DOI: 10.1111/jmp.12431
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and serum biochemistry data on southern brown howler monkeys (Alouatta guariba clamitans) in captivity in Brazil

Abstract: Background: Physiological values reflect the health condition and responses of individuals to handling in captivity. The aim of this study was to establish hematological and serum biochemistry parameters of clinically healthy animals of the Alouatta guariba clamitans subspecies. Methods:We collected blood samples from adult males and females kept at the Center for Biological Research of Indaial after chemical containment with 3.9 mg/kg of tiletamine hydrochloride and zolazepam.Results: Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
3
12
1
Order By: Relevance
“…This hypothesis is supported by the species differences in RBC count in the present work and in a previous study in wild populations 57 that showed higher RBC count in Sapajus lidibinosus compared to A. caraya. Although we were unable to compare RBC count between sexes due to heteroscedacity, previous studies have reported a greater RBC count in males than females in innumerous primate species, including S. apella, 58 S. lidibinosus, 59 Alouatta guariba clamitans, 60 A. azarae infulatus 10 and S. collinsi. 11 These sex differences have been associated with the stimulatory effect of testosterone on erythropoiesis, and the inhibitory effect of estrogen.…”
Section: Discussionmentioning
confidence: 87%
“…This hypothesis is supported by the species differences in RBC count in the present work and in a previous study in wild populations 57 that showed higher RBC count in Sapajus lidibinosus compared to A. caraya. Although we were unable to compare RBC count between sexes due to heteroscedacity, previous studies have reported a greater RBC count in males than females in innumerous primate species, including S. apella, 58 S. lidibinosus, 59 Alouatta guariba clamitans, 60 A. azarae infulatus 10 and S. collinsi. 11 These sex differences have been associated with the stimulatory effect of testosterone on erythropoiesis, and the inhibitory effect of estrogen.…”
Section: Discussionmentioning
confidence: 87%
“…We sampled animals that appeared healthy and that required management actions in captivity for biometric data collection, tagging, and translocation. After overnight fasting (12–14 h), we restrained these individuals physically and immediately anesthetized them with an intramuscular combination of tiletamine‐zolazepam (Zoletil 50 ® , Virbac, Brazil; 3.6 mg/kg) 20 . Subsequently, we subjected each individual to a complete physical examination by palpation, inspection (body mass and rectal temperature), and auscultation of the cardiorespiratory system 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Disease surveillance work can help detect new outbreaks and monitor the direction in which such outbreaks move, as well as host expansion, and also is a key aspect of managing ex-situ populations of Alouatta within a One Conservation framework (5,7). Disease surveillance can occur through serology and molecular biology for specific diseases, coprology, necropsies, overall health evaluation with extensive clinical data collection, and in conjunction with ongoing behaviors studies which can be combined with data available for human populations (4)(5)(6)(8)(9)(10)(11)(12)(13)(14).…”
Section: Leveraging Ex-situ Populationsmentioning
confidence: 99%
“…Baseline research on biochemical and hematological values in wild howler monkeys is needed to assess population health and the impact of anthropogenic activities, this has been done in Mexico, French Guiana, and Brazil ( 10 13 ). Similarly, possible lead poisoning due to anthropogenically driven habitat loss has been evaluated in Mexico ( 40 ) which deserves investigation in other countries in the natural range of howlers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation